Faktor-Faktor yang Berhubungan dengan Kematian Pasien TB MDR Selama Masa Pengobatan di Indonesia Tahun 2015-2017 - Zulfa Ayuningsih; Tri Yunis Miko Wahyono (Pro Health Jurnal Ilmiah Kesehatan, 2019)
The incidence of TB cases in Indonesia in 2014 was 399 per 100,000 people with a mortality rate due to TB of 41 per 100,000 population. The incidence of MDR TB in Indonesia is 1.9% of new cases and 12% of cases are from previous treatment. This study discusses the factors associated with MDR TB patient deaths during treatment in Indonesia. This study used a retrospective cohort design. Data were obtained from 33 MDR TB Referral Hospitals in 2015-2017. The research subjects were data on patients who had ≥15 years of age, were diagnosed with positive MDR TB, and had complete data. Sample selection is done by total sampling method. The dependent variable is death, while the independent variables of this study are age, gender, discussion, treatment, sputum gradation at the beginning of treatment, sputum conversion in the first two months, and the number of resistance. The analysis carried out consisted of descriptive analysis, Kaplan Meier, and Cox regression. The probability of survival of MDR TB patients is 94.8% at 6 months of treatment; 91.2% at 12 months of treatment; 90% at 18 months of treatment; 87% at 24 months of treatment, 83.6% at 30, 36, 42, and 48 months of treatment. Multivariate analysis, obtained variables that support statistics with the death of MDR TB patients> old> 45 years the risk of death is 1.71 times faster with patients who increase ≤45 years. and the amount of OAT resistance> 2 risk of compensation is 0.71 times faster than patients who have OAT resistance 2. Efforts to find out early TB patients against drugs at the age of ≤45 years are expected to reduce the morbidity and mortality of MDR TB patients during treatment.